The Impact of a Team-Based Learning Intervention on Healthcare Student’s Readiness towards Interprofessional Education; A Quasi-Experimental Study - Sana Shah; Maryam Akram; Junaid, Syed Muhammad; Siddiqui, Sana; Rehman, Saadia; Umbrin, Izza (Pakistan Armed Forces Medical Journal, 2023)
Objective: This study assesses the impact of an innovative Interprofessional Education (IPE) intervention, involving teambased learning session, on healthcare students’ readiness for IPE in Pakistan. Study Design: Quasi-experimental Study. Place and Duration of Study: Islam Medical & Dental College, Islam College of Nursing, Pharmacy & Physiotherapy, Sialkot Pakistan, from Apr to Sep 2023. Methodology: A Team-Based Learning (TBL) intervention for Interprofessional Education (IPE) was conducted with various healthcare discipline students, employing convenience sampling. The TBL included forming multidisciplinary teams, Individual Readiness Assurance Tests (IRAT), Team Readiness Assurance Tests (TRAT), and problem-solving exercises. Inclusion criteria required both pre and post Readiness for Interprofessional Learning Scale (RIPLS) questionnaire completion, resulting in 104 responses for statistical analysis. Paired t-tests within each discipline & subscale determined statistical significance (p ≤0.05) using SPSS Version 26. Learning gains were calculated per Barwood et al.’s method. Results: Ceiling effects were evident, reflecting high pre-intervention performance. The overall mean score increased from 74.49±10.6 pre-intervention to 76.87±10.4 post-intervention, although the change was statistically insignificant (p-value= 0.518).A substantial 23% increase in learning gains was observed. Conclusion: This research highlights the promising impact of IPE interventions and suggests their feasibility in enhancing Pakistan’s healthcare education. The positive impact of the intervention calls for a structured and unified IPE curriculum in Pakistani health education institutions. This step will enhance readiness for IPE, improving healthcare outcomes in Pakistan.